Inside Cover: Endo‐α‐Mannosidase‐Catalyzed Transglycosylation (ChemBioChem 14/2017). (28th June 2017) - Iwamoto, Shogo; Kasahara, Yuta; Yoshimura, Yayoi; Seko, Akira; Takeda, Yoichi; Ito, Yukishige; Totani, Kiichiro; Matsuo, Ichiro
Abstract : The inside cover picture shows a transglycosylation reaction catalyzed by Golgi endo ‐α‐mannosidase (G‐EM). We have demonstrated that G‐EM hydrolysis activity can be employed to mediate transglycosylation by using α‐fluorinated glucosyl mannoside as a donor. Systematic screening of various point mutants revealed that the E407D mutant had excellent transglycosylation activity. This optimized mutant is a versatile tool for synthesizing glucosylated high‐mannose‐type glycans. More information can be found in the communication by I. Matsuo et al. onpage 1376 in Issue 14, 2017 (DOI:10.1002/cbic.201700111 ).